Changes in mechanical properties and durability indices of concrete undergoing ASR expansion. (10th August 2020) - Diab, S.H.; Soliman, A.M.; Nokken, M.R.
Highlights: Fineness and physical properties of fused silica has a crucial role in the performance. Stiffness damage test results are highly affected by the degree of degradation. Ultrasonic pulse velocity has a highly sensitive for ASR damage. Carks formation has dominant effects on NDT results for ASR damaged concrete. Abstract: This research focuses on correlating the degree of expansion as a result of Alkali-Silica Reaction to mechanical properties and durability indices of hardened concrete. Degradation of six concrete mixtures incorporating Spratt aggregate with and without fused silica stored at 38 °C and 95 ± 5% RH were monitored for 12 months. Compressive and tensile strength decreased with time and the decreases became very significant as expansion progressed. There was no overall relationship found between strength and expansion for all mixtures. Linear correlations were observed between expansion with a modulus of elasticity and Poisson's ratio. Both the Stiffness Damage Index and the Plasticity Index show notable increases up to approximately 0.4% expansion with small increases beyond that level. Ultrasonic pulse velocity showed a strong correlation to expansion regardless of the mixture. Rapid chloride permeability showed an increase in the total charge passed as a function of time, and hyperbolic relationships best expressed the correlation between Rapid chloride penetration and expansion tests.